Changes in soil respiration components and their specific respiration along three successional forests in the subtropics. (16th January 2016) - Huang, Wenjuan; Han, Tianfeng; Liu, Juxiu; Wang, Gangsheng; Zhou, Guoyi
Summary: Understanding how soil respiration components change with forest succession is critical for modelling and predicting soil carbon (C) processes and its sequestration below‐ground. The specific respiration (a ratio of respiration to biomass) is increasingly being used as an indicator of forest succession conceptually based on Odum's theory of ecosystem development. However, the hypothesis that specific soil respiration declines with forest succession remains largely untested. We used a trenching method to partition soil respiration into heterotrophic respiration and autotrophic respiration ( R H and R A ) and then evaluated the specific R H and specific R A in three successional forests in subtropical China. Our results showed a clear seasonality in the influence of forest succession on R H, with no significant differences among the three forests in the dry season but a higher value in the old‐growth forest than the other two forests in the wet season. R A in the old‐growth forest tended to be the highest among the three forests. Both the specific R H and specific R A decreased with the progressive maturity of three forests. Our results highlight the importance of forest succession in determining the variation of R H in different seasons. With forest succession, soil microbes and plant roots become more efficient to conserve C resources, which would result in a greater proportion of C retained in soils. Abstract : Lay Summary